Notary Liability for Typographical Errors in Authentic Deeds from the Perspective of Legal Certainty - Maydiaz, Nauval Ihza; Huda, Miftakhul (Dinasti Research, 2026)
Typographical errors in authentic deeds are often perceived merely as correctable administrative mistakes with no significant legal consequences. However, in practice, such errors may alter the substance of the legal agreement and potentially cause losses to the parties involved. This raises a critical question regarding the liability of notaries as public officials and the extent to which typographical mistakes may affect the legal certainty of authentic deeds. This study aims to analyze notary liability for typographical errors and its implications for legal certainty and legal protection of the parties. This research employs a normative juridical method using statutory, conceptual, and case approaches. The statutory approach examines the provisions of the Law on Notary Office (UUJN) regarding notarial responsibility. The conceptual approach discusses theories of legal liability and legal certainty as developed by Gustav Radbruch and Hans Kelsen. Meanwhile, the case approach reviews court decisions related to administrative errors committed by notaries in the drafting of deeds. The study concludes that typographical errors cannot always be deemed minor, particularly when they affect the substance of the deed. Notaries may be held liable when such errors result in legal uncertainty or losses for the parties. Therefore, the enforcement of the prudential principle and the establishment of corrective mechanisms are essential to ensure legal certainty and accountability in notarial practice.